School Re-Openings after Summer Breaks in Germany Did Not Increase SARS-CoV-2 Cases - Ingo E. Isphording; Marc Lipfert; Nico Pestel (Institute of Labor Economics (IZA), 2020)
This paper studies the effect of the end of school summer breaks on SARS-CoV-2 cases in Germany. We exploit variation in the staggered timing of summer breaks across federal states which allows us to implement an event study design. We base our analysis on official daily counts of confirmed coronavirus infections by age groups across all 401 German counties. We consider an event window of two weeks before and three weeks after the end of summer breaks. Over a large number of specifications, sub-group analyses and robustness checks, we do not find any evidence of a positive effect of school re-openings on case numbers. On the contrary, our preferred specification indicates that the end of summer breaks had a negative effect on the number of new confirmed cases. Three weeks after the end of summer breaks, cases have decreased by 0.55 cases per 100,000 inhabitants or 27 percent of a standard deviation. Our results are not explained by changes in mobility patterns around school re-openings arising from travel returnees. We conclude that school re-openings in Germany under strict hygiene measures combined with quarantine and containment measures have not increased the number of newly confirmed SARS-CoV-2 infections.
Keywords: I12; I18; I28; 330; COVID-19; schooling; education; Germany